Analisis Efisiensi Keuangan Daerah Pasca COVID-19 dengan Pendekatan Data Envelopment Analysis (DEA) di Indonesia - Nadila Fitriansyah; Marselina Marselina; Dedy Yuliawan (CV. Bimbingan Belajar Assyfa, 2026)
Following the COVID-19 pandemic, regional governments in decentralized Indonesia face critical pressures to optimize limited public spending while accelerating socioeconomic recovery. This study evaluates the relative efficiency of regional fiscal management across 34 provinces in Indonesia from 2021 to 2025. Utilizing an output-oriented Data Envelopment Analysis (DEA) under the Variable Returns to Scale (VRS) assumption, the framework maps five fiscal inputs (education, health, road, subsidy, and personnel expenditures) against three development outputs (Gross Regional Domestic Product, Human Development Index, and non-poor population percentage). The results reveal significant regional disparities, with the number of efficient provinces fluctuating between 11 and 14, culminating in 14 fully efficient provinces by 2025. While frontiers like DKI Jakarta and East Kalimantan consistently demonstrated optimal resource utilization, regions such as Papua, West Papua, and East Nusa Tenggara persistently exhibited the lowest efficiency scores. Furthermore, the Returns to Scale analysis indicates that most underperforming provinces operated under Increasing Returns to Scale (IRS), suggesting substantial latent potential to maximize developmental outcomes without expanding budget allocations. In conclusion, enhancing expenditure quality, targeting structural budget execution, and minimizing resource slack are imperative to bridge regional disparities and foster equitable national development.